Cover Feature: Fast Screening Method for Nitrogen Reduction Reaction (NRR) Electrocatalytic Activity with Rotating Ring‐Disc Electrode (RRDE) Analysis in Alkaline Environment (ChemCatChem 24/2020). Issue 24 (23rd November 2020) - Ferrara, Marcello; Bevilacqua, Manuela; Tavagnacco, Claudio; Vizza, Francesco; Fornasiero, Paolo
Abstract : The Cover Feature represents an old fashioned record player with the rotating ring disk used to detect ammonia at a platinum ring electrode, achievable during a cyclic voltammetry only at the NH3 oxidation potential. In their Full Paper, M. Ferrara et al. explain that a Rotating Ring Disk Electrode (RRDE) setup can be used to qualitatively determine in‐situ if an electrocatalyst is active toward the Nitrogen Reduction Reaction (NRR) in alkaline environments, thanks to the high sensibility of the platinum ring electrode. The results show that, through different electrochemical measurements, it is possible to study the stability of the catalyst itself, and to detect possible subproducts of the nitrogen reduction reaction, such as N2 H4 . More information can be found in the Full Paper by M. Ferrara et al.